2020
DOI: 10.1109/temc.2019.2931369
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Error Correction Codes Against Harsh Electromagnetic Disturbances: Fault Mechanisms

Abstract: Modern safety-critical systems rely heavily on robust communication channels. Even though these communication channels can be protected by Error Detection and Correction Codes, vulnerabilities caused by False Negatives still exist. These False Negatives can be caused by harsh electromagnetic disruptions and are detriment to overall safety. This paper considers the construction and structure of Triplication-based Error Correction Codes to find the most EMI-resilient code. Each code is tested and simulated in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…From [4], it can be concluded that a simple triplication method is the most effective in terms of limiting the number of False Negatives under harsh EMI disturbances. The simple triplication method is denoted as TEC, since it sends the data three times (Triplication), without inversion (Equal) and bit by bit (Close together).…”
Section: Characteristics Of the Baselinementioning
confidence: 99%
See 4 more Smart Citations
“…From [4], it can be concluded that a simple triplication method is the most effective in terms of limiting the number of False Negatives under harsh EMI disturbances. The simple triplication method is denoted as TEC, since it sends the data three times (Triplication), without inversion (Equal) and bit by bit (Close together).…”
Section: Characteristics Of the Baselinementioning
confidence: 99%
“…In [4], a selection of Error Detection and Correction Codes (EDCCs) -which are frequently used in FS Engineeringhave been studied and compared in the context of harsh EMI. That research determined the fault mechanisms associated with continuous-wave electromagnetic disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations